Optimization of Silylation for Parabens Determination by Gas Chromatography-Mass Spectrometry - Djatmika, Rosalina; Ding, Wang-Hsien (ALCHEMY, 2016)
A low cost, environmental friendly and convenient method for parabens derivatization using Gas Chromatography-Mass Spectrometry (GC-MS) analysis is investigated. Derivatization is needed to enhance the thermal stability, detectability, and volatility of parabens to make them amenable for gas chromatographic analysis. This method involved on-line derivatization by silylating reagent: N-Methyl-N-tert-butyldimethylsilyltrifluoroacetamide (MTBSTFA), N,O-bis (trimethylsilyl) trifluoroacetamide (BSTFA), N-methyl-N-trimethylsilyltrifluoroacetamide (MSTFA), and N,O-bis(trimethylsilyl)acetamide (BSA). The variables affected the derivatization process, such as, types and volumes of silylating reagents, injection port temperature, and purge-off time, were evaluated to obtain the optimal condition for determination of parabens. The Relative Response Factors (RRF) was used as a parameter of parabens derivatization efficiency to obtain the best compromise condition of each variable. On a comprehensive level, a comparison of the optimal condition of each silylating reagent was evaluated. Moreover, 1 µL of MSTFA  at 260°C of injection port temperature and 2.5 min purge-off time (in splitless mode) obtained the most effective of derivatization process.